Magnetic nickel nanostructure as cellulase immobilization surface for the hydrolysis of lignocellulosic biomass - Rashid, Shah Samiur; Mustafa, Abu Hasnat; Mohd Hasbi, Ab. Rahim; Gunes, Burcu (Elsevier Ltd, 2022)
In this research, a magnetic reusable nickel nanoparticle (NiNPs) supporting materials were prepared for cellulase enzyme immobilization. The immobilized cellulase showed high activity recovery, large & fast immobilization capacity and improved pH & temperature tolerance. The excellent stability and reusability enabled the immobilized cellulase to retain 84% of its initial activity after ten cycles. At 2 mg/mL enzyme concentration, highest 93% immobilization efficiency was achieved within two hours of immobilization. When the treatment temperature reached 40 °C and pH 5, the immobilized cellulase exhibited highest residual activity. The immobilized cellulase could be separated from the solution by a magnetic force. This study introduced a novel supporting material for cellulase immobilization, and the immobilized cellulase poses a great potential in the hydrolysis of lignocellulosic biomass which can used as an easily applicable and sustainable pre-treatment step for advanced biofuel production.